Adult Children and the Transition of Aging Parents. (4th May 2018) - Gilbert, Sarah M.; Nemeth, Lynne; Amella, Elaine; Edlund, Barbara; Burggraf, Virginia
Abstract: This study explores the experiences of adult children as they transition their functionally and/or cognitively declining aging parents from independent living to supervised housing. A qualitative grounded theory approach was used to chronicle the experiences of adult children as their caregiving responsibilities intensified and their parents' health declined. Purposive, snowball sampling was used to enlist adult children ( n = 16) who were in the process of transitioning an aging parent from an independent living situation to one providing assistance with everyday care and tasks. Semi-structured telephone interviews were conducted and designed to follow a pattern of increased frailty of the parent(s) and escalating involvement of the adult child. Two major themes emerged from the data: Changing places and everlasting love. Adult children began to intervene when cognitive or physical declines compromised the safety and well-being of the older adult and began to assume responsibility for day-to-day needs. As disabilities intensified, adult children relied on siblings, friends, social services, and health care providers to assist in planning and implementing caregiving responsibilities. Deep respect and abiding love of the aging parent(s) sustained the adult child throughout the caregiving experience.